Association Between Breastfeeding and Nutritional Status In Children With Congenital Heart Disease At Dr. Soetomo General Hospital - Safina Fairuz Salwaa; Taufiq Hidayat; I Gde Rurus Suryawan (Syntax Literate, 2022)
Congenital heart disease (CHD) is a congenital condition caused by a lack of heart development during the fetal stage. There is a notion that children with CHD have low nutritional status due to their condition. Nutritional input, energy requirements, dietary components, and prenatal circumstances impact a person's nutritional status. An analytical observational design with a cross-sectional approach was used in this research. Data were obtained via medical records and questionnaires posed to the patients' guardians who had provided informed consent. The Chi-square test and multivariate logistic regression analysis were used to analyze the data. The study was conducted on 62 subjects. There were 74.19% of subjects with acyanotic CHD and 25.81% with cyanotic CHD. 61.29 % of the subjects were exclusively breastfed for the first six months. The Chi-Square test revealed a relationship between breastfeeding and the nutritional status of children with CHD, with p = 0.0001 (p<0.05). The multivariate logistic regression analysis showed the significance of the type of CHD suffered by the subjects was 0.003 (p<0.05). There is a significant association between breastfeeding for the first six months and the type of CHD suffered by children with their nutritional status at Dr. Soetomo General Hospital.